2011
DOI: 10.1016/j.jhsa.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Distal Radioulnar Joint Instability in Distal Radius Fractures

Abstract: A radiographic finding of a normalized DRUJ gap on posteroanterior views was the most important predictor to identify DRUJ instability accompanying unstable distal radius fractures. The relative risk of instability increases by 50% when the ratio of DRUJ widening increases by 1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 21 publications
(31 reference statements)
0
56
0
4
Order By: Relevance
“…However, well-designed studies consistently denied the association between symptomatic DRUJ instability and the ulnar styloid fracture in distal radius fractures [15,35,39,44]. Recently widening of the DRUJ gap was identified as an independent risk factor for DRUJ instability in distal radius fractures [8]. In this study, we tried to identify clinical and radiographic factors associated with DRUJ instability in distal radius fractures.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, well-designed studies consistently denied the association between symptomatic DRUJ instability and the ulnar styloid fracture in distal radius fractures [15,35,39,44]. Recently widening of the DRUJ gap was identified as an independent risk factor for DRUJ instability in distal radius fractures [8]. In this study, we tried to identify clinical and radiographic factors associated with DRUJ instability in distal radius fractures.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies investigate the factors associated with DRUJ instability in the setting of distal radius fractures. Lindau and Aspenberg found no radiographic parameters associated with DRUJ instability [24], but Fujitani et al [8] reported that widening of the DRUJ gap was the only risk factor for DRUJ instability. These discrepancies between studies arise from differences in study setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations